Constituent effect on mechanical performance of crushed demolished construction waste/silt mixture. (2nd August 2021) - Deng, Yongfeng; Xu, Chenchen; Marsheal, Fisonga; Geng, Xueyu; Chen, Yonggui; Sun, Honglei
Highlights: CDW-silty soil mixture can be a reliable and eco-friendly alternative as subgrades materials. 50% was the threshold content in mass of CDW-silty soil mixture in this investigation. Failure pattern was identified by the destruction morphology and contact force network. This mixture behaves same as naturally deposited rocks, i.e. pebbled sandstone or granular rock etc. Abstract: With the development of urbanisation, massive crushed demolished construction wastes (CDW) have been generated, leading to environmental and disposal problems. In order to recycle the waste efficiently, an engineering sustainable CDW disposal was carried in Dajiangdong area, Hangzhou China. CDW was used to stabilize the deposited loose silt for feasible constructions and liquefaction preventions. The mix comprised of silt, CDW and cement was designed to be used as subbase material with higher density and less void. The vibro-compaction was used to rearrange the grain distributions within the mixtures to improve the mechanical performance at an optimal constituent, and then the numerical simulation was performed to evaluate the internal mechanism of the admixture under compression. The result shows that the workability of CDW-silt-cement mixture has an optimum of CDW content at 50% in order to achieve the best engineering performance. Moreover, the cement, which intergrades the silt and supplies the cementation among the coarse CDW, are not only generate cohesion but also provide anti-erosion effect.